81‐5: Late‐News Paper: Pb‐free Blue‐emitting 0D Cs3Cu2I5 with High PLQY of 90%. Issue 1 (29th May 2019) - Jun, Taehwan; Sim, Kihyung; Iimura, Soshi; Sasase, Masato; Kamioka, Hayato; Kim, Junghwan; Hosono, Hideo
Abstract : Recently, perovskites such as CsPbX3 (X=Cl, Br, I) are promising for optoelectronic devices. However, there are still critical issues that hinder their practical use: one is the toxicity of lead (Pb) and the other one is low PLQY due to small exciton binding energy. To solve these problems, we explored new metal halide luminescent materials. Here, we broadened a perspective into copper halide based materials with low‐dimensional electronic structures. Consequently, we newly found a solutionprocessable 0D Cs3 Cu2 I5 that exhibits blue emission ( 445 nm) and significantly high PLQY s; 90% and 60% for single crystal and thin films, respectively. In this paper, we also report electroluminescence (EL) device using 0D Cs3 Cu2 I5 thin films.